The Analysis of QR Code-Based Books to Develop Cognitive Aspects of 5-6 Year Old Children - Nina Veronica; Sofi Yunianti; Naili Saida; Harun Harun; Arif Rohman (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
Appropriate learning media is one of the keys to successful education, especially in early childhood education. This study aims to develop QR code-based books as a means of developing the cognitive abilities of children aged 5-6 years. The research approach uses research and development (RD) with development models that can be carried out in the classroom, one of which is the ADDIE research model (analysis, design, development, implementation, evaluation). Data collection techniques in this study used observation and questionnaires. The results of the expert's assessment showed that the media got a proportion of 79% in the "Good" category with an interval of 61% -80%. The results of the material expert's assessment got a proportion of 78% in the good category with an interval of 61% -80%. the results of the implementation of QR Code-based books through the results of the assessment that has been carried out by the teacher show that 85% of children get good categories. So it can be concluded that QR Code-based books show proper use in developing children's cognitive development.